2000
DOI: 10.1177/026988110001400208
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin autoreceptor function and antidepressant drug action

Abstract: This article briefly summarizes, within the context of a brief review of the relevant literature, the outcome of our recent rat microdialysis studies on (1) the relative importance of serotonin (5-HT)1A versus 5-HT1B autoreceptors in the mechanism of action of 5-HT reuptake blocking agents, including putative regional differences in this regard, and (2) autoreceptor responsiveness following chronic SSRI administration. First, our data are consistent with the primacy of 5-HT1A autoreceptors in restraining the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 84 publications
6
113
0
2
Order By: Relevance
“…However, the increase of 5-HT level was similar in rats treated for 13 days with escitalopram (10 mg/kg/day) and citalopram (20 mg/kg/day) (Ceglia et al, 2004). Although no microdialysis studies were undertaken in hippocampus following long-term administration of these two SSRIs, several other studies have shown that the net impact of different SSRIs on extracellular 5-HT could vary with brain regions, such as between the frontal cortex and hippocampus (Malagié et al, 1996;Hervas and Artigas, 1998; see for a review Hjorth et al, 2000) depending on their innervation by DRN vs median raphe nucleus, respectively. The greater efficacy of escitalopram compared to citalopram in increasing extracellular 5-HT in hippocampus, if any, does not appear to result in differential increase in tonic activation of postsynaptic 5-HT 1A receptors, as was shown with other antidepressant, thus suggesting that other mechanisms are involved.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the increase of 5-HT level was similar in rats treated for 13 days with escitalopram (10 mg/kg/day) and citalopram (20 mg/kg/day) (Ceglia et al, 2004). Although no microdialysis studies were undertaken in hippocampus following long-term administration of these two SSRIs, several other studies have shown that the net impact of different SSRIs on extracellular 5-HT could vary with brain regions, such as between the frontal cortex and hippocampus (Malagié et al, 1996;Hervas and Artigas, 1998; see for a review Hjorth et al, 2000) depending on their innervation by DRN vs median raphe nucleus, respectively. The greater efficacy of escitalopram compared to citalopram in increasing extracellular 5-HT in hippocampus, if any, does not appear to result in differential increase in tonic activation of postsynaptic 5-HT 1A receptors, as was shown with other antidepressant, thus suggesting that other mechanisms are involved.…”
Section: Discussionmentioning
confidence: 96%
“…Although complex, the combination of several adaptive changes such as desensitization of the 5-HT 1A receptors in the raphe nucleus, amygdala and hypothalamus, normosensitive 5-HT 1A receptors in hippocampus and cortex, and the interplay between 5-HT soma and nerve terminal might contribute, at least in part, to the antidepressant responses of SSRIs (for a review see Hjorth et al, 2000;Hensler, 2003). Nevertheless, the results obtained from raphe dorsalis suggest that the gradual recovery of normal firing activity of DRN neurons, which was reported to underlie the delayed effect of SSRI on 5-HT neurotransmission , is in accordance with the earlier onset of action of escitalopram vs citalopram in animal models of depression and anxiety (Sánchez et al, 2003a, b;Fish et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Most augmentation strategies are derived from the hypothesis that chronic selective serotonin reuptake inhibitor (SSRI) treatment results in a desensitization of presynaptic serotonergic (5-HT) autoreceptors. This blunted autoreceptor control leads to increased effects of SSRIs on central serotonin levels in time, which is postulated to parallel the antidepressant effect (Hjorth et al, 2000;Blier, 2001;Blier et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, several such augmentation strategies have been developed. These add-on strategies range from antagonism of serotonergic autoreceptors like 5-HT 1A and 5-HT 1B (Hjorth et al, 2000;Blier et al, 1998;Artigas et al, 1994Artigas et al, , 1996Bosker et al, 2001;Celada et al, 2001;Cremers et al, 2000a, b), but also comprise heteroceptors such as adrenoceptors (Bengtsson et al, 1998;Szabo and Blier, 2001;Besson et al, 2000;Hopwood and Stamford, 2001;Bortolozzi and Artigas, 2003;Pudovkina et al, 2003;Rouquier et al, 1994;Amargos-Bosch et al, 2003;Weikop et al, 2004;Gobert et al, 1997;Gobert and Millan, 1999;De Boer et al, 1996), 5-HT 2A receptors (Szabo and Blier, 2002), GABA B receptors (Abellan et al, 2000;Slattery et al, 2005;Mombereau et al, 2004;Nakagawa et al, 1996), and substance P receptors (Guiard et al, 2004), to mention but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated activation of this receptor has been shown to induce a desensitization phenomenon, a mechanism that has been associated to the delayed therapeutic action of selective 5-HT reuptake inhibitors. 17,19 Previous anecdotal reports on the absence of 5-HT1A expression in serotonergic neurons can be found in the literature, but most studies lack convincing proof and/or thorough quantification. To address this question, we used a combination of histochemistry techniques, and molecular detection with single-cell resolution.…”
mentioning
confidence: 99%